2001
DOI: 10.1046/j.1469-0691.2001.00062.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of antibiotic prophylaxis for the prevention of intravascular catheter-related infection

Abstract: Intravascular catheters have become essential tools for the management of patients in modern medical practice, but there are complications. In particular, catheter-related infection remains a major cause of nosocomial infection and primary septicemia. The development of preventive strategies to reduce the incidence of catheter-related infection is an important goal for all health providers. Over recent years, significant advances in prophylactic measures for the prevention of catheter-related infection have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 106 publications
(118 reference statements)
1
12
0
1
Order By: Relevance
“…Our search yielded 63 published reports (figure 1); 56 studies were excluded because they evaluated lock solutions other than vancomycin [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46], did not have a control group [47][48][49][50], used a lock solution for treatment rather than prevention [45,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65], did not use a randomized, controlled study design [66][67][68][69], assessed the utility of a lock solution for prevention of BSI with only 1 type of organism [70], were reviews [19,20,56,[71][72][73][74][75]...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our search yielded 63 published reports (figure 1); 56 studies were excluded because they evaluated lock solutions other than vancomycin [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46], did not have a control group [47][48][49][50], used a lock solution for treatment rather than prevention [45,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65], did not use a randomized, controlled study design [66][67][68][69], assessed the utility of a lock solution for prevention of BSI with only 1 type of organism [70], were reviews [19,20,56,[71][72][73][74][75]...…”
Section: Resultsmentioning
confidence: 99%
“…A promising approach to preventing these infections has involved instilling (i.e., locking) an antiinfective solution into the device lumen or lumens to prevent colonization of the intraluminal surface by suspended planktonic-phase contaminants [19][20][21]. Because the majority of BSIs associated with IVDs are caused by gram-positive organisms, particularly coagulase-negative staphylococci [22][23][24][25], vancomycin in combination with heparin has been the best studied prophylactic lock solution.…”
mentioning
confidence: 99%
“…With respect to these observations, the use of current sterile barriers seems to be insufficient. Among different strategies for the prevention of CVC-related infection, use of antimicrobial impregnated catheters is considered [23]. A metaanalysis of studies concerning impregnated catheters has found a significant reduction in the incidence of CVCrelated infection with the use of coated catheters in intensive care unit patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown contamination rates of 28.8% and 52% without the use of antibiotics (19,21) and of 13.3% with antibiotic prophylaxis (21). Antibiotic prophylaxis, although effective, may lead to resistance among coagulase-negative staphylococci (22). In a meta-analysis on the use of antimicrobial impregnated catheters in adults, a decrease in catheterrelated bacteraemia of 2.2% was found; however, again the risk of antimicrobial resistance was emphasized (22).…”
Section: Discussionmentioning
confidence: 99%